Line Balancing and Workload Redistribution to Reduce Overtime in a Mixed-Model Production System at CV XYZ - Agatha Hannabel Avananta Puteri; Erni Puspanantasari Putri; Jirayut Nakhowong; Pariwat Jantarangsee (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2026)
CV XYZ is a spare parts manufacturing company in Surabaya facing production line imbalance in a mixed-model line producing Spur Gear, Shaft Pump, and Housing Bearing. The initial conditions showed Workstation 2 Lathe Machine (1 meter) as the primary bottleneck with a workload of 212.67% and Full Time Equivalent value of 2.31 due to simultaneous processing of two products. This resulted in line efficiency of 66.61 percent, Balance Delay of 33.39 percent, Smoothness Index of 325.68, and 885 man-hours of overtime costing IDR 18,585,000 during October 2025–March 2026. Based on three improvement iterations, the third was selected as the optimal solution with a 6-workstation configuration through optimization of Lathe Machine (1 meter). The proposed improvement increased line efficiency to 85.91 percent, reduced Balance Delay to 14.09 percent, and lowered the Smoothness Index to 87.78. Workforce validation showed 6 operators are sufficient, with Workstations 1 through 4 within the normal category. Second lathe machine optimization reduced overtime to 548 hours, cutting overtime costs IDR 7,077,000. Total operational costs decreased from IDR 112,930,975 to IDR 107,562,767, yielding net saving of IDR 5,368,208 or 4.75 percent without additional labor or investment in new machinery.